Physical fitness testing component of KINETI-KIDS I project in public and private schools in Metro Manila (2008)
Physical fitness tests on 432 school children from 4 selected pilot schools were conducted for two consecutive school years using standard methods. The study was aimed to determine the fitness level of the KinetiKids students after the implementation a physical activity program has been completed. Push up, trunk lift, partial curl up, sit-and-reach, zipper test, broad jump, and T-run were included in the tests. The push-up scores of children from public schools consistently improved during the four periods, indicating hat their upper arm and upper body muscles became stronger at the course of the study, All other event parameters showed an erratic trend along four periods. Significant improvements in the paired sample tests implied development of stronger upper body and arm, lower back extensor and leg muscles for the students in both school types as well as more flexible hamstring muscles for those in the private schools. Significant improvements on push-up and trunk-lift were observed among students from public schools in the second year. Similar improvement was noted in push-up activity of private school children. Results indicate that schools should promote promote regular physical activity and exercise, adequate and proper nutrition to sustain health and fitness of children.
Keywords: Physical fitness for children